2006
DOI: 10.1016/j.juro.2006.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Pilot Study of Intravesical Apaziquone (EO9) for Superficial Bladder Cancer

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…Furthermore, the predominant metabolite found in blood and urine following intravenous administration was the inactive, aziridine ring open metabolite EO5A [54,59]. Following intravesical administration, two clinical studies have investigated the pharmacokinetic and safety of apaziquone [60,61]. In the first of these studies [61], apaziquone was administered 2 weeks after TURBT and for the first six patients entered into the trial, each received an escalating dose of apaziquone with one dose per week (for a total of 6 weeks).…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the predominant metabolite found in blood and urine following intravenous administration was the inactive, aziridine ring open metabolite EO5A [54,59]. Following intravesical administration, two clinical studies have investigated the pharmacokinetic and safety of apaziquone [60,61]. In the first of these studies [61], apaziquone was administered 2 weeks after TURBT and for the first six patients entered into the trial, each received an escalating dose of apaziquone with one dose per week (for a total of 6 weeks).…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%
“…Following intravesical administration, two clinical studies have investigated the pharmacokinetic and safety of apaziquone [60,61]. In the first of these studies [61], apaziquone was administered 2 weeks after TURBT and for the first six patients entered into the trial, each received an escalating dose of apaziquone with one dose per week (for a total of 6 weeks). At all doses administered, no detectable levels of apaziquone or EO5A were found in the blood.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%
“…As for porfiromycin, preclinical data supported the clinical development of E09, but the clinical utility of the agent appeared compromised by very poor biodistribution and pharmacokinetics 312 . However, E09 has had a recent clinical revival in superficial bladder cancer where intravesical administration circumvents the delivery and clearance issues 313,314 . Development of the nitroimidazoles progressed with the 2-nitroimidazole RSU1069: a modified misonidazole derivative that acts as a bi-functional alkylating agent by virtue of an aziridine ring 315 .…”
Section: Prototype Agents In the Development Of Bioreductive Drugsmentioning
confidence: 99%
“…109 The relative stability of the compound and rapid pharmacokinetic elimination of the drug make it an intriguing agent for use in NMIBC, and Phase I/II trials have confirmed minimal local and systemic toxicity. 9,110,111 In a recent update of their Phase I study, Jain et al reported that of the eight patients who achieved a complete response, 50% relapsed over a median follow-up of 31 months. Of note, the recurrence-free interval significantly increased following apaziquone administration compared with historic recurrence intervals pretreatment.…”
Section: Apaziquonementioning
confidence: 99%